2021
DOI: 10.1029/2020gl091461
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Variability of Surface Chlorophyll During the Evolution of Gulf Stream Rings

Abstract: We investigate how the near‐surface chlorophyll (CHL)‐a evolves in Gulf Stream (GS) warm‐core rings (WCRs) and cold‐core rings (CCRs) using multi‐platform satellite observations. Averaged CHL anomaly (CHLA) within the rings exhibits both positive and negative linear trends during the evolution of the WCRs while negative trends dominate in CCRs. This difference is associated with a variety of physical processes occurring during the evolution process. Meanwhile, eddy‐centric analysis reveals four spatial pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…This CE appears reasonably close to the coast, near the limits of coastal processes for several of the satellite data products used. EKE values suggest that this CE was a cold‐core Gulf Stream ring, which are known for their high EKE and productivity (Gangopadhyay et al., 2019; Kang & Curchitser, 2013; Lai & Richardson, 1977; Leterme & Pingree, 2008; Ning et al., 2021). While SLA, EKE, and Chl‐a are notably high within this eddy, the SST and SSS values inside the eddy appear largely unremarkable compared to those surrounding it, which is not unusual for a Gulf Stream ring.…”
Section: Resultsmentioning
confidence: 99%
“…This CE appears reasonably close to the coast, near the limits of coastal processes for several of the satellite data products used. EKE values suggest that this CE was a cold‐core Gulf Stream ring, which are known for their high EKE and productivity (Gangopadhyay et al., 2019; Kang & Curchitser, 2013; Lai & Richardson, 1977; Leterme & Pingree, 2008; Ning et al., 2021). While SLA, EKE, and Chl‐a are notably high within this eddy, the SST and SSS values inside the eddy appear largely unremarkable compared to those surrounding it, which is not unusual for a Gulf Stream ring.…”
Section: Resultsmentioning
confidence: 99%
“…Satellite chlorophyll measurements could miss some of the impact that WCRs have on the shelf/slope chlorophyll. Surface chlorophyll anomalies within rings have also been shown to have inconsistent responses to the rings (Ning et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Mesoscale eddies are ubiquitous and play fundamental roles in physical‐biological‐biogeochemical interactions in the ocean (McGillicuddy, 2016). Their importance in transporting and redistributing nutrients has been long recognized (e.g., Chen et al., 2020; Ning et al., 2021; Wang et al., 2021), while the existing observed nitrate profiles are not enough to resolve the effects of most eddies. The temperature and salinity profiles are much more than nitrate profiles, and a few studies have applied the Core Argo observed profiles to investigate the effects of mesoscale eddies on heat transport (e.g., Ning et al., 2019; Zhang et al., 2014).…”
Section: Discussionmentioning
confidence: 99%